Development of somatic cell nuclear transfer techique for biomedical and agricultural research : report - Mongkol Techakumphu (Chulalongkorn University, 2009)
To develop somatic cell nuclear transfer by using the rabbit as a mode in biomedical and agricultural research. The experiments are described in nine chapters: Chapter 1: Introduction, Chapter 2: Superovulation and oocyte recipient production in rabbits, Chapter 3: A technique for adult and foetal fibroblast cell culture, for donor cell preparation in somatic nuclear transfer, Chapter 4: Preliminary studies on somatic cell nuclear transfer in rabbits, Chapter 5: In vitro development of rabbit cloned embryos using adult fibroblast cells, after post-activation treatment with cyelohexamide and 6-dimethlylaminopurine, Chapter 6: Development of rabbit cloned embryos using cumulus cells, serum-starved and non-starved fibroblast cells, as the donor nucleus, Chapter 7: Development of cloned embryos from adult and foetal rabbit fibroblast cells, Chapter 8: A comparison of cell fusion technique and intracytoplasmic donor cell injection for producing cloned rabbit embryos, Chapter 9: Conclusion. In conclusion, the whole processes of somatic nuclear transfer using cell fusion technique was developed. This included recipient oocyte preparation, donor cell preparation, enucleation of recipient oocytes, fusion and activation, nuclear transfer and in vitro culture of cloned oocytes to the morula and blastocyst stage. A failure of in vitro development was observed when using intracytoplasmic donor cell injection in both mice or rabbits. Further studies will focus on the type of donor cells and interspecies cloning, embryonic stem cell development and the application of nuclear transfer in endangered species.